2013
DOI: 10.4236/health.2013.51017
|View full text |Cite
|
Sign up to set email alerts
|

The “Brain Drain”: Factors influencing physician migration to Canada

Abstract: Context: Higher income countries have an average physician density of 300 physicians per 100,000 people. In stark contrast, lower income countries have an average physician density of 17 physicians per 100,000 people. A major cause of this discrepancy is the migration of healthcare professionals from lower income to higher income countries, a phenomenon colloquially known as the "brain drain". Objective: To explore factors that led International Medical Graduate (IMG) physicians to leave their home countries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
(27 reference statements)
1
14
0
Order By: Relevance
“… 11 In our previous survey of IMGs who were fully licensed and working in independent practice in Ontario, physicians felt that the best way to stem brain drain from lower-income countries would be to include more continuing medical education opportunities in source countries, addressing issues such as safety and quality of life, and importantly, more accurate information about the lack of opportunities in Canada. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 In our previous survey of IMGs who were fully licensed and working in independent practice in Ontario, physicians felt that the best way to stem brain drain from lower-income countries would be to include more continuing medical education opportunities in source countries, addressing issues such as safety and quality of life, and importantly, more accurate information about the lack of opportunities in Canada. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Most questions were close-ended, but open-ended questions allowed participants to describe influential push and pull factors, challenges they had faced in trying to obtain a residency training spot, activities they had participated in while waiting for a residency spot, and any recruitment methods they may have encountered, and to make suggestions regarding how low-income and middle-income countries could retain physicians and other health professionals. The survey was created based on the existing literature, particularly with regard to causes for physician migration, and was an adaptation of our previously published survey, which had been pretested for clarity, relevance of questions, and survey duration with staff physicians in the Department of Family and Community Medicine at St Michael’s Hospital who had global health expertise and/or were foreign-trained 10. The survey took approximately 10 minutes to complete.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables such as social, cultural, economic, professional issues, bureaucracy and globalization are some causes of migration of skilled human resources ( 10 , 11 ). Lufterz et al, conducted a study in 2013 in which they found that the most common causes of migration were socioeconomic and political, and that the most important reason for selecting migration to Canada was family issues ( 12 ). Nouri Hekmat et al, revealed that from the viewpoint of students of Iran University of Medical Sciences, important factors affecting migration included economic and education considerations as well as administrative, professional, globalization, social and cultural factors ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ontario is home to a large number of internationally trained medical doctors (ITMDs). Data from 2014 indicate that Ontario may have 6,000 ITMDs (Lofters, Slater, & Thulien, 2013;Taghizadegan, 2013). Despite the influx of highly educated ITMDs, a multitude of barriers prevent ITMDs from securing employment as medical doctors.…”
Section: Introductionmentioning
confidence: 99%